2002
DOI: 10.1095/biolreprod67.4.1189
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Temperature Induces Region-Specific p53-Independent Apoptosis in the Cauda Epididymidis of the Mouse1

Abstract: It is widely accepted that temperature regulates gene expression and function in the epididymis. However, the significance of reduced temperature of the scrotum in cell survival had not often been examined. Our hypothesis was that the experimental increase of the temperature could induce apoptosis. Using a surgical method that consists of surgically reflecting the cauda epididymidis in the abdomen, we have been able to show that this is the case. Apoptosis was examined by histologic procedures and by visualiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 60 publications
(73 reference statements)
1
11
0
1
Order By: Relevance
“…The role of p53 in mediating apoptosis in the male genital tract has been demonstrated in several mice lines [28,29,42]. However, p53-independent apoptosis is suggested in the prostate and seminal vesicles by androgen withdrawal or in the rat epididymis by deprivation of luminal factors [3,11,14,38]. Previous studies indicated that Bcl-2 family proteins are involved in the induction or prevention of apoptosis [12,33,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The role of p53 in mediating apoptosis in the male genital tract has been demonstrated in several mice lines [28,29,42]. However, p53-independent apoptosis is suggested in the prostate and seminal vesicles by androgen withdrawal or in the rat epididymis by deprivation of luminal factors [3,11,14,38]. Previous studies indicated that Bcl-2 family proteins are involved in the induction or prevention of apoptosis [12,33,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…73 Such low apoptosis may reflect the presence of anti-apoptotic B-cell lymphoma-2 (Bcl-2) and absence of pro-apoptotic Fas. 74 The normal mouse epididymis expresses p53 and the apoptosis effector caspase 3, 75 yet apoptosis in this organ following cryptepididymis and castration is independent of p53 and Fas/FasL, 75,76 as is rat epididymal apoptosis after efferent duct ligation. 73 Senescence Another mechanism of intrinsic tumour suppression is age-independent 'senescence', a signal transduction programme leading to irreversible arrest of cell proliferation, accompanied by distinct changes in cellular phenotype.…”
Section: Apoptosismentioning
confidence: 99%
“…Furthermore, spermatozoa were not observed in the epididymal lumen. Several factors may contribute to the pathology observed in the ectopic epididymis in this study, including exposure to a higher temperature as reported by Jara et al (2002).…”
Section: Discussionmentioning
confidence: 49%